Penguatan Pendidikan Iman dalam Jemaat: Tantangan dan Pendekatannya di Gereja Kontemporer - Jerry Donni (Institut Agama Kristen Negeri Palangka Raya, 2023)
This research intends to analyze the strengthening of faith education in congregations in contemporary churches. It cannot be denied that the impact of globalization is a challenge and at the same time has changed the pattern of faith education in the church. The literature review method is used to discuss and answer these problems. The results of the study reveal that in strengthening the faith education of the congregation in the contemporary church, it is necessary to pay attention to the following important principles. The church must be able to transform from the traditional model to a more dynamic and responsive model. This is not only related to teaching methods, but also about how to convey religious messages so that they remain relevant to the context of the daily lives of worshipers. Then, the importance of utilizing technology as an educational tool cannot be ignored. Churches need to utilize digital platforms, social media, and other technologies to reach worshipers, especially millennials who are highly connected to the digital world. Effective communication and a deep understanding of the needs of various worshipers are key to overcoming the challenges of conveying Christian values.